Hati dalam Perspektif Al-Qur`An dan Hadits: Sebuah Studi Pustaka - Barni, Mahyuddin; Rosadi, Khumaini; Iskandar (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2023)
The heart, as the king that moves body parts, must be cared for regularly, because the heart is a benchmark for the quality of a human being. The heart is the birthplace of human feelings. Human nature is determined by one's heart. Rasulullah SAW always taught his people to always maintain purity and cleanliness of heart in order to avoid heart disease and despicable qualities. Because if you don't take care of it, it will be dangerous for yourself and others. If the heart is left alone, not cared for by enlightening good advice, it can become susceptible to becoming sick. If a person's heart has been infected with a disease, such as envy, then he cannot feel peace and tranquility in life. His heart was always restless every time he saw other people getting pleasure. It seems like he doesn't want other people to get pleasure from God, as if he had to have that pleasure himself.